Structural and compositional comparison of Si₃N₄ ceramics with different fracture modes - Döblinger, M; Winkelman, G; Dwyer, C; Marsh, C; Kirkland, A; Cockayne, D; Hoffmann, M (Elsevier, 2006)
Two similarly processed yttrium oxide-doped Si₃N₄ ceramics containing differing amounts of amorphous phase are studied. Differences in the fracture mode of these two materials have been analysed structurally and compositionally by transmission electron microscopy. In agreement with the chemistry of the starting materials, similar glass compositions are observed for the two samples from energy dispersive X-ray analysis. In both samples the yttrium-to-oxygen count ratio is lower in intergranular films than in pockets. The interfacial structure of prismatic crystal faces is similar in pockets and in intergranular films, with the main structural difference being a reduction in order as a function of distance from the prism plane, which is related to the film thickness. Atomic positions at the interface unequivocally related to yttrium attachment could not be identified. The results indicate that a low total amount of glass can play a role in dictating the film thickness. Furthermore, the possible influence of the width of intergranular films on the fracture mode is discussed.